MIFOLOGIK TAFAKKUR VA UNING EVOLUTSIYASI: XAOSDAN KOSMOS SARI ONGLI HARAKAT. - Sheraliyeva Muhabbat (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This research provides an extensive academic inquiry into the essence of mythological thinking and its intricate historical evolution across the timeline of human civilization. The study posits that mythology is not merely a collection of archaic fables, but a primary and sophisticated cognitive framework that enabled early humanity to interpret existence, institutionalize social hierarchies, and establish a coherent cosmic order. By analyzing the structural transition from "mythos" to "logos," the article illuminates the evolutionary trajectory of human consciousness—from symbolic-metaphorical perceptions to the rigorous domains of rational-logical reasoning. Furthermore, the findings demonstrate that mythological archetypes remain deeply embedded as a psychological substrate within modern cultural constructs, shaping contemporary ideologies, art, and collective identity patterns.